LEGALITAS USAHA UNTUK PENGEMBANGAN UMKM DI DESA KARANGSEGAR - Septiani Ningrat, Nova; Rofieq, Ainur; Turmudi Zy, Ahmad (An-Nizam, 2023)
The current condition of MSMEs is recommended to have business legality for their products. However, in Karangsegar Village, it is still minimal and the community does not understand the importance of business legality in the market. Community service activities aim to improve and assist Karangsegar Village MSME players in marketing products and business development through legality. The method of implementing the service applies socialisation, training and mentoring methods until the MSME actors have obtained a business identification number and halal certification. The results of community service are that MSME actors obtain the right business legality, build consumer confidence, and the existence of certification and legality helps improve reputation and increase product competitiveness.